PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN - Ni Komang Mega Antari Dewi; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2021)
Dividend policy is a decision to determine how much profit the company receives will be distributed to shareholders in the form of dividends. The purpose of this research is to determine whether this dividend policy was affectted by profitability, company size and liquidity. The population in this study were manufacturing companies on the Indonesia Stock Exchange in 2015-2019. The type of research used is quantitative and the sampling technique uses purposive sampling method, so that the sample obtained is 130 samples from 26 manufacturing companies that are listed consecutively on the Indonesia Stock Exchange during 2015-2019. The analysis method used in this research is multiple linear regression analysis. Based on the results of the simultaneous analysis test, profitability, firm size and liquidity have an effect on dividend policy and partially profitability and firm size have a positive effect on dividend policy, while liquidity has no effect on dividend policy.